Three dialogues against Lactantius critical Latin edition, English translation, introduction, and notes - Antonio da Rho 1398-1450 (Brill's studies in intellectual history, 2023)
"Antonio da Rho's Three Dialogues against Lactantius (1445) followed the lead of Jerome and Augustine yet went well beyond patristic concerns. During the Middle Ages Lactantius' works, while largely neglected, had enjoyed moments of intense interest and study. From the death of Lactantius (325) to his broad Quattrocento recovery, many profound cultural and intellectual shifts had transpired. Consequently, Rho's dialogues engage topics arising from scholastic and other debates in jurisprudence, cosmology, astrology, geography, philosophy, and theology. He was convinced that insights from these fields would elucidate errors of Lactantius that his readers had overlooked. This reveals much about the cultural and intellectual developments that shaped readers' efforts to recover, comprehend, and define Lactantius as an author. Significantly, the list of Lactantius' errors discussed in the dialogues was printed with nearly every edition of Lactantius through the sixteenth century and beyond"--